ON A SOLUTIONS OF ONE CLASS OF ALMOST HYPOELLIPTIC EQUATIONS - Hakobyan, G.H. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2015)
We prove that if P(D)=P(D_1,D_2)=_αγ_α D_1^α_1D_2^α_2 is almost hippoelliptic regular operator, then for enough small δ>0, all solutions of equation P(D)u=0 from L_2,δ(R^2) are entire analytical functions.